LAW AND SOCIETY: INTERACTIONS AND RELATIONSHIPS - Maryati, Sri; Qotadah, Hudzaifah Achmad; Achmad, Adang Darmawan; Syafril, Syafwendi (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
The presence of law within society is of paramount importance, as it serves to regulate human behavior. The law necessitates subjects, or implementers, namely the members of society, creating a reciprocal relationship between law and society. Consequently, law can function both passively and actively to control human actions, with the ultimate goal of guiding society toward deliberate and improved change. There are numerous objectives behind the creation of laws in societal life and the reasons why society necessitates their existence. Primarily, laws are established to foster peace, tranquility, welfare, and to provide legal certainty, ensuring that each individual can attain their rightful entitlements and justice. The comprehensive realization of these legal objectives within society, however, is contingent upon public adherence to the law. Therefore, it can be posited that a society devoid of guidelines, such as laws, would likely generate numerous disputes, resulting in a chaotic and arbitrary existence. This research adopts a qualitative approach and is analyzed descriptively The findings underscore the inherent interdependence between law and society, revealing that the efficacy of law is contingent upon its reception and implementation by society at large. Consequently, the symbiotic nexus between law and society emerges as indispensable for the attainment of societal order and justice. The symbiotic relationship between law and society is characterized by a reciprocal exchange, wherein society provides the necessary context and adherence for the efficacy of law, while law, in turn, serves as a guiding framework for societal behavior and interaction. This symbiosis is essential for fostering a cohesive and harmonious social fabric, wherein individuals coexist within a structured framework of rights, obligations, and responsibilities.